Ultrasonic response of a piezoelectric aluminum nitride film deposited on silicon. Issue 2 (4th March 2017) - Lemlikchi, S.; Asmani, M.; Djelouah, H.; Schaaf, P.; Hopfeld, M.; Aouimeur, W.
ABSTRACT: An aluminum nitride (AlN) thick film for ultrasonic transduction was deposited on a silicon wafer by magnetron sputtering. A columnar structure with uniform elemental depth profiles with 40 at.% to 60 at.% (Al-N) concentrations and with a c-axis preferential orientation was observed by X-ray diffraction. The ultrasonic response of the Al/AlN/Si overmoded resonator was characterized from 1.24 MHz to 2 GHz using a vector network analyzer. The time domain transform and the gate features of the vector network analyzer were used to characterize the AlN thick film capabilities in the time and frequency domains. The results show that the obtained resonator operates over a broad frequency range with a central frequency at approximately 930 MHz and a 738 MHz bandwidth at -6 dB. The results were compared with those obtained from a one-dimensional simulation to highlight and predict the AlN response features. A comparison was performed to validate the experimental measurements and to validate the circuit modeling. Overall agreement between the experiment values and the simulation was observed.